Rhetorical Devices Used by Bill Gross in Presenting His Speech on Start-up Success - Rieyan Dhitama Lee (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study, using a qualitative approach, was conducted to find out the rhetorical devices used by Bill Gross when presenting his speech on start-up success, including the function of each of the devices used. The presentation was divided into three parts: introduction, body, and conclusion. In conducting the research, the writer used the theory proposed by Harris (2018). The findings showed that the speaker used all of the rhetorical devices under the three categories, namely: Emphasis, Transition, and Clarity. Each device also has different functions depending on the context of the presentation: to raise the topic’s importance, to provide emphasis, to provide clarity, to maintain the audience’ curiosity, to show the impression of spontaneity, to elaborate details, to help the audience understand better, to anticipate question, and to anticipate ambiguity. In conclusion, the rhetorical devices, particularly hypophora and amplification as the mostly used ones, were applied by Bill Gross to better deliver his presentation.